1976
DOI: 10.1021/ac60367a007
|View full text |Cite
|
Sign up to set email alerts
|

Multielement atomic spectrometry with a computerized vidicon detector

Abstract: A computerized vidicon flame spectrometer is described along with Its application to a simultaneous determination of four serum electrolytes. Data acquisition, transfer, storage, and manipulation have been greatly improved by the computer addition. Operator input has been minimized while the programming has incorporated such features as automatic least-squares polynomial curve fitting, "spectral stripplng", background corrected peak signal measurements, and internal standard corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The OMA console being a hard wired computer system permits the use of signal averaging techniques to improve the precision of measurement, and to allow the removal of practically all types of spectral interferences. A recently completed computer interface provides for a more rapid data acquisition and manipulation system facilitating a more extensive use of the ratio method in flame spectrometric analyses (20). The examples which follow explore the capabilities of the vidicon-OMA system as they apply to the analysis of real samples.…”
Section: Resultsmentioning
confidence: 99%
“…The OMA console being a hard wired computer system permits the use of signal averaging techniques to improve the precision of measurement, and to allow the removal of practically all types of spectral interferences. A recently completed computer interface provides for a more rapid data acquisition and manipulation system facilitating a more extensive use of the ratio method in flame spectrometric analyses (20). The examples which follow explore the capabilities of the vidicon-OMA system as they apply to the analysis of real samples.…”
Section: Resultsmentioning
confidence: 99%
“…One-dimensional systems are based on a window concept (5), resulting in a compromise between resolution and wavelength coverage. Under certain favorable circumstances (6)(7)(8), widely spaced spectral lines may sometimes be monitored without unduly increasing the size of the wavelength window (and thereby suffering a loss in resolution) by monitoring spectral lines in overlapping orders. This approach, however, is not successful in every case, and the limited wavelength window obtained by mounting an image detector at the focal plane of a conventional spectrograph remains the most serious problem associated with this optical arrangement (4).…”
mentioning
confidence: 99%
“…State-of-the-art multichannel detectors such as vidicons, photodiode arrays, charge coupled devices, etc. are being evaluated for their present spectroscopic capabilities (7)(8)(9)(10)(11), although it is recognized that significant improvements will be forthcoming in this rapidly developing field. Previous reports from this and other laboratories have detailed the development and characterization of such systems employing silicon vidicon tubes for spectroscopic measurements (7)(8)(9)(10)(12)(13)(14)(15)(16)(17)(18). These research efforts have shown that the combination of simultaneous multiwavelength detection and digital multichannel signal processing provides numerous analytical benefits.…”
mentioning
confidence: 99%